PEMBINAAN PETANI DI DESA SONGAN, KECAMATAN KINTAMANI-BANGLI MENGENAI PENGGUNAAN PESTISIDA - N. M. Utami Dwipayanti; M. Ayu Hitapretiwi Suryadhi; N K. Sutiari; I N. Sujaya; I Agus Gelgel Wirasuta; N T. Suryadhi (Buletin Udayana Mengabdi, 2012)
The knowledge of farmers on pesticides and its association on health and the environment still remains an issue. Located in the rural area of Bali, the village of Songan, Kintamani, Bangli with its fertile soil accommodates many farm lands. The counseling and assistance included 20 farmers during their working hours to allow direct observation. The counseling and assistance targeted at issues regarding safe uses of pesticides and its association to health and the environment. The knowledge of participants was evaluated by pre- and post-test. Less than a half (40%) were able to identify an association between pesticide use and health, while almost all do not know the chronic effect of pesticides to health and/or the environment. Recommendations target health care facilitators are expected to continue counseling and assistance to the farmers and others in order to maintain a healthier and more sustainable future.